Kajian Yuridis Dasar Pertimbangan Hakim Pada Putusan Nomor 29/Pid.Sus-Tpk/2020/PN.Jkt.Pst tentang Penggunaan Alat Bukti Elektronik dalam Proses Tindak Pidana Korupsi di Indonesia - Muhammad Nasrulloh; Leni Dwi Nurmala (Postgraduate University of Merdeka Malang, 2026)
This study aims to analyze the legal basis for judges' considerations in accepting and assessing electronic evidence in Decision Number 29/Pid.Sus-TPK/2020/PN.Jkt.Pst and evaluate its compliance with the principle of legal certainty in criminal evidence. Using normative legal methods based on evidentiary theory, legal certainty theory, and legal system theory, this study examines the process of accepting electronic evidence in court. The results indicate that judges prioritize the authenticity, integrity, and reliability of electronic evidence, such as emails, conversation recordings, and transaction data, which have undergone digital forensic examination to ensure the absence of manipulation. Judges also refer to the provisions of Law Number 11 of 2008 concerning Electronic Information and Transactions and jurisprudence that recognizes electronic evidence as valid evidence. These considerations reflect the principle of legal certainty because the process of accepting evidence is carried out in accordance with applicable procedures and legal frameworks. However, this study emphasizes the importance of strengthening regulations and technical standards so that the mechanism for accepting electronic evidence can be implemented more consistently and standardized throughout the Indonesian judicial system.